An orthotropic multi-surface damage-plasticity FE-formulation for wood: Part II – Numerical applications. (November 2020) - Benvenuti, E.; Orlando, N.; Gebhardt, C.; Kaliske, M.
Highlights: We consider damage under tensile/shear stresses and plasticity. The model transitions from the continuous damage plasticity regime of Part I to a regularized XFEM regime. The transition is smooth. Failure is correctly captured. Abstract: The present study investigates the modelling capabilities offered by the multi-surface damage-plasticity FE-formulation illustrated in Part I [1] when integrated with a regularized extended finite element model. The aim is to tackle discontinuous displacements and interfaces. In particular, we show how to embed a regularized discontinuity within an element, carry out the transition from the continuous to the regularized discontinuous regime and obtain physically consistent results. We present a wide set of applications ranging from brittle to ductile failure, displaying the effectiveness of the proposed FE-approach versus the experimental results.